Scale Measurement of Health Primary Service Utilization among the Migrant International Population - Consuelo Cruz-Riveros; Alfonso Urzúa; Carolina Lagos (MDPI AG, 2023)
In this article, we analyze the internal structure of the scale for experience in exercising the right to health care (EERHC), based on the focus from the World Health Organization (WHO) on the right to health care, from the perspective of international migrants, in Chile. The methodology was an instrumental study (n = 563) conducted to analyze the psychometric properties of the EERHC scale. Its reliability and internal consistency were evaluated, while the exploratory structural equation modeling (ESEM) model and confirmatory factor analysis (CFA) were used to identify the structure of relationships between the variables measured. The item-dimension correlations obtained present levels of r ≥ 0.3, and the Cronbach's α and McDonald's ω presented ranges >0.9, considered to be acceptable on all models. Results: the model was selected for presenting a good fit index χ2 = 24,850, df = 300, p = 0.000; RMSEA = 0.07; CFI = 0.97; TLI = 0.95; and SRMR = 0.03. The evidence obtained lets us conclude that the scale has forty-five items and four dimensions. The findings demonstrate a good internal structure and are useful to measure primary health care service utilization based on the framework.